(untitled) (KULT_online, 2013)
The 16 essays in this volume emerged out of the conference "Das Bild als Ereignis", organized in February 2011 at the University of Heidelberg. This volume proposes a reading of late medieval art in light of Hans-Georg Gadamer’s approach to the eventfulness of an artwork. The collection of essays argues for possible ways to tie in Gadamer’s account of aesthetic experience as a dialogical interaction between the beholder and an ever-changing artwork (p. 11) with current art historical practice. Interdisciplinary perspectives from the fields of philosophy and the history of art explore the processes through which medieval art might be understood as an interlocutor by the beholder today.